3-Dimensional quantitative structure-activity relationship and molecular docking studies of tetrasubstituted pyrazole derivatives as inhibitors of cyclooxygenase-2 - Singh, Kulwinder; ., Monika; Verma, Neelam (International Journal of Research in Medical Sciences, 2017)
Background:Design and development of new drugs is simplified and made more cost-effective because of the advances in the concepts of Quantitative Structure-Activity Relationship (QSAR) studies. A methodology of QSAR studies is one of the approaches to the rational drug design. Methods:3-Dimensional QSAR studies were performed on a series of tetrasubstituted pyrazole derivatives by using Scigress Explorer software suite. Docking studies of these compounds were also performed to understand the interactions with amino acid residues of COX-2 protein. Results:The multiple linear regression analysis was used to correlate the physicochemical descriptors with the COX-2 inhibitory activity of 24 training set of compounds and the best QSAR model was developed. The best model was validated using leave-one-out method and found to be statistically significant, with coefficient of determination (r2) of 0.835. This model was further used to predict the COX-2 inhibitory activity of 10 test set of compounds. Docking analysis revealed that most of the compounds formed H-bond interactions with amino acid residues of COX-2 protein (PDB ID: 1CX2). Predicted pIC50 value of one of the test compounds was 7.048 and it showed H-bond interactions with His90 & Tyr355 residues. Conclusion:The present study shall help in rational drug design and synthesis of new selective COX-2 inhibitors with predetermined affinity and activity and provides valuable information for the understanding of interactions between COX-2 and the novel tetrasubstituted pyrazole derivative compounds.